2-(Benzo[d]thiazol-2-ylsulfonyl)-1-(4-bromophenyl)ethanone - Loghmani-Khouzani, H.; Hajiheidari, D.; Robinson, W.T.; Kia, R. (International Union of Crystallography, 2010)
In the title molecule, C(15)H(10)BrNO(3)S(2), the dihedral angle between the benzothiazole ring system and the benzene ring is 67.57 (12)degrees. The crystal structure is stabilized by weak intermolecular C-H center dot center dot center dot O interactions. In addition, there is an intermolecular Br center dot center dot center dot C [3.379 (3) angstrom] contact which is shorter than the sum of the van der Waals radii of these atoms.